Hijab woman visualization in commercial shampoo advertisement: Critical discourse analysis - Erika, Puspita Magda; Anam, Moh Khoirul (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
The appearance of shampoo advertisements with female models wearing hijabs is a unique phenomenon. This study aims to reveal the message contained in the commercial shampoo Rejoice 3in1 Perfect Cool which uses a hijab model. This research is a qualitative descriptive study. Using the theory of Systemic Functional Linguistics and the Critical Discourse Analysis approach with the three-dimensional model of Norman Fairclough, the researchers wanted to find out what message the text producers wish to convey to the audience. The data in this study are advertisements for Rejoice hijab shampoo. The data was got from YouTube. The data were then downloaded and transcribed so that text data can be obtained. The data were then analyzed using the theory of Systemic Functional Linguistics. From the data that has been analyzed, it was found that the message contained in the advertisement shows that the text producer wants to show that Rejoice 3-in-1 cool shampoo can give a cool impression on the head even though the person who uses the shampoo is wearing a hijab. This indicates that the shampoo is very suitable for use even by people who use hijab, especially in the tropics. The data also shows that the visualization of the hijab model in advertisements that are shown and given Indonesian narrative text seems to be adapted to the majority of Indonesian people who are Muslim, moreover this advertisement is shown during Ramadan.